DISTANCE EDUCATION: REALITIES OF TEACHING AND LEARNING - Kravets, Samiilo; Morozova, Viktoriia; Morozova, Yaroslava (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
This article is devoted to teaching through distance learning. In March 2020, a disaster came to Ukraine, which covered Europe, to which this disaster came from China. This problem is called the coronavirus. At first, there was panic as to how the educational process would take place in such conditions, and when the first shock passed, everyone remembered distance learning. And then came the full-scale war. And distance learning came to the rescue again.